Cyperus rotundus L.: Traditional uses, phytochemistry, and pharmacological activities. (4th November 2015) - Peerzada, Arslan Masood; Ali, Hafiz Haider; Naeem, Muhammad; Latif, Muhammad; Bukhari, Asad Hussain; Tanveer, Asif
Abstract: Ethno-pharmacological relevance: Cyperus rotundus L. (Cyperaceae) is a medicinal herb traditionally used to treat various clinical conditions at home such as diarrhea, diabetes, pyresis, inflammation, malaria, and stomach and bowel disorders. Currently, it is one of the most widespread, problematic, and economically damaging agronomic weeds, growing wildly in various tropical and subtropical regions of the world. The present paper summarizes the available information that will aid in future medicine preparation by identifying active ingredients and their mode of action for a specific therapeutic activity using the latest technologies. Material and method: This review article is based on the information available on the phytochemical, toxicological, and pharmacological studies on and traditional uses of C. rotundus . The present paper covers the literature available particularly from 2000 to 2015 online (Google Scholar, PubMed, ScienceDirect, Scopus, SpringerLink, and Web of Science) and in books on phytochemistry, ethnopharmacology, and botany of this plant. Results: Phytochemical and pharmacological studies revealed the significance of C. rotundus as an antiandrogenic, antibacterial, anticancerous, anticonvulsant, antidiabetic, antidiarrheal, antigenotoxic, anti-inflammatory, antilipidemic, antimalarial, antimutagenic, antiobesity, antioxidant, anti-uropathogenic, hepatoprotective, cardioprotective, neuroprotective, and nootropic agent. This is the most investigated plant worldwide due to the higher concentration of active ingredients in the form of essential oils, phenolic acids, ascorbic acids, and flavonoids in the tuber and rhizomes. Unfortunately, this significant plant species has not been assessed under improved cultivation conditions with the aim of conservation in natural habitats and high quality. Conclusion: Reports can be found on the ehtnobotanical use of C. rotundus in atherosclerosis, aging, apoptosis, cancer, cystitis, epilepsy, hirsutism, nociception, prostatitis, and genotoxicity disorders. The phytochemical and pharmacological activities of C. rotundus have supported its traditional as well as prospective uses as a valuable Ayurvedic plant. Previous researches focuses on the phytochemistry, biological properties and clinical application of rhizomes and tubers of C. rotundus . However, such studies on the other parts of this medicinally important plant are still quest to be investigate. Furthermore, future study should aim at confirming the clinical activities and safety of this plant before being used for the development of new therapeutic agent in human subjects. Graphical abstract: